Seasonal changes in physical capacities of elite youth basketball players - Matulaitis, K.; Sirtautas, D.; Kreivyte, R.; Butautas, R. (Journal of Physical Education and Sport, 2021)
The aim of this study was to investigate the differences in seasonal changes in physical capacities of elite youth basketball players during preparatory and competitive periods. A total of 17 elite youth male basketball players from second and third basketball leagues of Lithuania (age: 17.8 ± 1.3 years; height: 198.5 ± 8.2 cm; body mass: 86.4 ± 8.6 kg) voluntarily participated in this study. All of these players also play for youth national teams. The players underwent testing 4 times: before preparatory period, after preparatory period, after first competitive round and after second competitive round. For each player, stage, countermovement jump (CMJ), countermovement jump with free arms (CMJ FA), 10-20 m sprint and lane agility tests were performed. Descriptive analysis was performed using the mean of the count of the event and standard deviation. The reliability of differences between averages was determined in accordance with the Student criterion for independent samples (the normality of distribution was tested by applying the Shapiro-Wilk criterion). In the assessment of the reliability of the results, the difference was deemed to be statistically significant when p < 0.05 (95% reliability). All statistical tests were performed using the software package IBM SPSS version 23.0 for Windows. This study showed that in elite youth basketball players, there were seasonal changes between testing before preparatory period and after second round competitive period, i.e., there was an increase in the indicators of CMJ and lane agility (p < 0.05) but not in CMJ FA and 10-20 m sprint indicators. Physical fitness tests (10- 20 m sprint test, CMJ, CMJ FA, and lane agility test) are essential for the development process of youth basketball players to allow coaches to determine whether players are developing in terms of physical fitness.